Genre of transcription in aspect of composer’s style (on the example of Oleksandr Nazarenko’s creativity) (International Journal of Scientific Research and Management (IJSRM), 2021)
This article considers theoretical and practical aspects of research of the transcription genre, grounds its stylistic properties, reliance on the model of other’s performance, double authorship, and action of composer’s interpretation. These issues are projected onto the timbre-texture complex in this genre as the most important factor of transcription. The material of the research was the concert arrangement of F. Lips and the transcription of A. Nazarenko to one original source – the play «Shivering Leaves» by P. Norrbak. Specificity of the analyzed musical material proposed in this article is the comparison of two arrangements – F. Lips and A. Nazarenko – in order to identify the distinctions between them, as well as the revelation of the individual-style spectra of the transcriptions genre in A. Nazarenko’s works. At this, it is noted that in creating the author’s version, A. Nazarenko relied not on the original Waltz by P. Norrbak, but on the F. Lips’ arrangement acting as a work model in this comparative analysis. In the analysis of the two versions, different methods of research are used, besides the comparative one – they are also interpretation, considering the problems of bayan performance; genre, and style, which characterize the compositional and dramatic features, genre-style specificity of musical exponents; organological, contributing to the research of the specificity of the instrument, here – bayan in the context of comparing its expressive possibilities in two plays. His research resulted in the identification of the principal distinctions in methods of artistic interpretation of two authors.